Effect of enhanced external counterpulsation therapy on myeloperoxidase in lowering cardiovascular events of patients with chronic heart failure (Medical Journal of Indonesia, 2013)
Background: Chronic heart failure (CHF) is a slowly progressive disease with high morbidity and mortality; therefore, the management using pharmacological treatments frequently fails to improve outcome. Enhanced external counterpulsation (EECP), a non-invasive treatment, may serve as alternative treatment for heart failure. This study was aimed to evaluate the influence of EECP on myeloperoxidase (MPO) as inflammatory marker as well as cardiac events outcome. Methods: This was an open randomized controlled clinical trial on 66 CHF patients visiting several cardiovascular clinics in Manado between January-December 2012. The subjects were randomly divided into two groups, i.e. the group who receive EECP therapy and those who did not receive EECP therapy with 33 patients in each group. Myeloperoxidase (MPO) as inflammatory marker was examined at baseline and after 6 months of observation. Cardiovascular events were observed as well after 6 months of observation. Unpaired t-test was use to analyze the difference of MPO between the two groups, and chi-square followed by calculation of relative risk were used for estimation of cardiovascular event outcomes. Results: MPO measurement at baseline and after 6 months in EECP group were 643.16 ± 239.40 pM and 422.31 ± 156.26 pM, respectively (p < 0.001). Whereas in non EECP group, the MPO values were 584.69 ± 281.40 pM and 517.64 ± 189.68 pM, repectively (p = 0.792). MPO reduction was observed in all patients of EECP group and in 13 patients (48%) of non-EECP group (p < 0.001). Cardiovascular events were observed in 7 (21.21%) and 15 (45.45%) of patients in EECP and non-EECP groups, respectively (p = 0.037). Conclusion: EECP therapy significantly decreased the level of MPO as inflammatory marker and this decrease was correlated with the reduction of cardiovascular events in CHF patients. (Med J Indones. 2013;22:152-60. doi: 10.13181/mji.v22i3.584)